Dilemma and Malgovernability in the Politics of Management of the Kulukubuk Waterfall Tourism Market in Siberut, Mentawai Islands Regency - Ahmad, Munawar; Samaloisa, Rijel (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2024)
This paper will explain some dilemmas and malgovernability on tourism governing in Kulukubuk tourism’s destination. Kulukubuk is the name of water fall located in Madobag’s forest, Siberut island, Mentawai district. Before state governance taking handled, Kulu kubuk have been a famous destination for tourism. Kulukubuk has exotic waterfall for relaxing and healing surrounded by rain forest tree. For Mentawai people, Kulukubuk has strong myth related their circle of life, they believe the water of Kulukubuk bring their body and also their properities will be blessed by Taika. In that time, Kulukubuk totally governing by local people and give back benefit to them. But, since 2019, state government totally govern Kulukubuk, and Tourism department of Mentawai was refining all facilitate for access to Kulu kubuk with better construction. After constructed, state government do not bring local people involve for governing. Until four years passed, Kulukubuk’s facilities was abandon, damaged and useless. It was portraying a malgovernability within, it is our reason why this paper written.